The avocado pear tree - Case, Bonita (Department of English Language and Literature, 2016)
For twenty years Elsie September has refused to visit her uncle, Hannie, a state patient at Valkenberg mental hospital. At her grandmother's insistence, she almost goes to see him one day, but she only gets as far as the building and cannot bring herself to go inside. Instead, she meets Shaun and, as a relationship develops, Elsie begins to tell him the stories of her childhood. But Elsie's relationship with Shaun is troubled and unbalanced. Before Elsie reaches the point in her narrative where she will explain why she refuses to see her uncle, she and Shaun part acrimoniously and he disappears. Elsie has, by now, become so caught up in the telling of her story that not even Shaun's disappearance can stop her from going back to the day her world changed beneath the sheltering arms of the avocado pear tree.